Lexical and Grammatical Cohesion in the Undergraduate Students’ Abstracts - Episiasi Episiasi; Wuri Syaputri; Suramto Suramto; Destina Kasriyati (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
This study aims to determine the lexical and grammatical cohesion of abstracts of STKIP PGRI Lubuklinggau students. The method used is a qualitative case study. The results showed that students made ungrammatical sentences, wrong prepositions, spelling errors, and improper cohesive devices. In conclusion, lexical and grammatical cohesion is used in the abstract. The repetition of words in lexical cohesion keeps the reader on track, while grammatical cohesion is used to describe available references, conjunctions, substitutions to make a good abstract. Keywords: Abstract, Grammatical Cohesion, Lexical